Microscopic Identification and Determination of Total Flavonoid Content of Moringa Leaves Extract and Ethyl Acetate Fraction (Moringa oleifera L.) - Annisa Fatmawati; Depita Sucianingsih; Riza Kurniawati; Muhammad Abdurrahman (Indonesian Journal of Pharmaceutical Science and Technology, 2021)
This research was conducted to identify simplicia microscopically, phytochemical screening and determination of total flavonoid content of extract and ethyl acetate fraction from Moringa (Moringa oleifera L.) leaves using UV-Visible Spectrophotometry method. The experimental design used in this study was to perform microscopic identification of Moringa leaf powder simplicia, make 96% and 70% ethanol extract and ethyl acetate fraction of Moringa leaves from 70% ethanol extract, then carry out phytochemical screening and determination of total flavonoid content with quercetin standards. Phytochemical screening on the ethyl acetate fraction of Moringa leaves included tests for the content of flavonoids, saponins, tannins and alkaloids. The results of microscopic identification of Moringa leaf simplicia showed the presence of calcium oxalate crystals in the form of rosettes, mesophyll and stomata. The result of determination of total flavonoid content in 96% ethanol extract was 16.69 ± 0.74% (w/w), 70% ethanol extract was 10.84 ± 0.49% (w/w), Moringa leaf ethyl acetate fraction 14 .45 ± 0.90% (w/w). The highest total flavonoid content was found in the 96% ethanol extract of Moringa leaves in accordance with the 2017 Indonesian Herbal Pharmacopoeia, that the thick extract of Moringa leaves containing no less than 6.30% (w/w) total flavonoids was calculated as quercetin.